P352High cholesterol diet deteriorates cardiac autophagy. (15th July 2014) - Giricz, Z; Varga, ZV; Csonka, C; Szucs, G; Adameova, A; Gottlieb, RA; Mentzer, RM; Ferdinandy, P
Abstract: Introduction: We have previously shown that autophagy is necessary for the ischemic preconditioning (IPC) of the heart and that IPC is compromised in the setting of hypercholesterolemia (HC). The mTOR pathway, an upstream modulator of autophagy, has been shown to be activated in HC. The purpose of this study was to test the hypothesis that HC results in down regulation of autophagy due in part to activation of mTOR signalling and to investigate whether HC modulates programmed cell death mechanism such as apoptosis and necroptosis in the heart. Methods: Male Wistar rats were fed either normal chow or with 2% cholesterol and 1% cholic acid-enriched diet for 10 weeks. HC rats exhibited a 41% increase in plasma total cholesterol level over that of rats fed standard chow (2.89mmol/L vs. 4.09mmol/L) at the end of diet period. Animals were sacrificed, hearts were excised and briefly washed out, then left ventricles were snap-frozen for determination of autophagy, mTOR pathway, apoptosis, and necroptosis-related proteins by Western blot. Results: HC was associated with a significant reduction in LC3-II and in Beclin-1 expression compared to control values. Consistent with mTOR activation, S6 phosphorylation, an mTOR target, was increased in HC animals (p=0.021). Bax/Bcl2 ratio and cleaved caspase-3 signal increases in HC animlas, while no difference in the expression of RIP3 or MLKL was detected between treatments. Conclusion: These data indicate that hypercholesterolemia suppresses basal cardiac autophagy and that the decrease in autophagy may be a result of an upregulated mTOR pathway; however the exact signaling mechanism is yet to be elucidated. Reduced autophagy was accompanied by signs of increased apoptosis, while cardiac necroptosis was not modulated by HC. Decreased basal autophagy and elevated apoptosis may be responsible for the loss of cardioprotection reported in hypercholesterolemic states.